2021
DOI: 10.1111/jsr.13339
|View full text |Cite
|
Sign up to set email alerts
|

Sleep‐related hypermotor epilepsy and non‐rapid eye movement parasomnias: Differences in the periodic and aperiodic component of the electroencephalographic power spectra

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Studies have shown that their respective parameterizations help clarify the possible confounding contribution of background arhythmic brain activity to the measurement of oscillatory components of neural activity ( Donoghue et al, 2021 ). For example, variability in the aperiodic slope and offset accounts for changes in the neural power spectrum along the lifespan ( Cellier et al, 2021 ; Schaworonkow and Voytek, 2021 ), covaries with clinical outcomes in a number of disorders ( Ostlund et al, 2021 ; Pani et al, 2021 ; Van Heumen et al, 2021 ; Wilkinson and Nelson, 2021 ), and predicts memory consolidation during sleep ( Helfrich et al, 2021 ) and individual differences in visuomotor learning ( Immink et al, 2021 ). Regarding the reliability and stability of these components, Pathania et al (2021) found that estimates of aperiodic components are consistent over intervals of at least seven days.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that their respective parameterizations help clarify the possible confounding contribution of background arhythmic brain activity to the measurement of oscillatory components of neural activity ( Donoghue et al, 2021 ). For example, variability in the aperiodic slope and offset accounts for changes in the neural power spectrum along the lifespan ( Cellier et al, 2021 ; Schaworonkow and Voytek, 2021 ), covaries with clinical outcomes in a number of disorders ( Ostlund et al, 2021 ; Pani et al, 2021 ; Van Heumen et al, 2021 ; Wilkinson and Nelson, 2021 ), and predicts memory consolidation during sleep ( Helfrich et al, 2021 ) and individual differences in visuomotor learning ( Immink et al, 2021 ). Regarding the reliability and stability of these components, Pathania et al (2021) found that estimates of aperiodic components are consistent over intervals of at least seven days.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the PSD decay in humans resulted to be steeper in conditions typically related with increased inhibition, such as NREM sleep ( He et al, 2010 , Miskovic et al, 2019 , Shen et al, 2003 ) or general anesthesia ( Colombo et al, 2019 ), when compared to wakefulness – as indexed by more negative SE values ( Freeman, 2006 , Freeman and Zhai, 2009 , Miskovic et al, 2019 , Pereda et al, 1998 ). Therefore, the use of SE is gaining popularity also in the study of neurologic conditions ( Belova et al, 2021 , Molina et al, 2020 , Pani et al, 2021 , Wilkinson and Nelson, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the PSD decay in humans resulted to be steeper in conditions typically related with increased inhibition, such as NREM sleep [10,25,26] or general anesthesia [17], when compared to wakefulnessas indexed by more negative SE values [25,[27][28][29]. Therefore, the use of SE is gaining popularity also in the study of neurologic conditions [30][31][32][33] Interestingly, more negative SE values (paralleled by reduced E/I ratio) were found over the affected hemisphere in rat models of stroke [34]. Since the SE captures EEG slowing, and is sensitive to alterations in the E/I balance, we expect it to be a reliable measure of the neurophysiological alterations in stroke.…”
Section: Introductionmentioning
confidence: 99%